(untitled) - Wiger, Donald E. (New York, 2001)
Outcomes assessment has become an increasingly critical component of contemporary mental health practice, yet most therapists receive little or no training in accepted outcomes assessment and documentation methods. Tracking Mental Health Outcomes fills this gap, providing step-by-step guidance on choosing the best outcomes-tracking methods and instruments for your practice. You'll see how to integrate them into everyday clinical procedures and use the data they supply to improve the quality of care you provide as well as fully comply with insurance company and regulatory agency requirements.
Keywords: Mental health services,Outcome assessment (Medical care),Dịch vụ sức khỏe tâm thần,Kết quả đánh giá (chăm sóc y tế)